Developing speaking materials based on contextual language teaching and learning for grade eleven students - Sugiyartanti, Sugiyartanti; Robiasih, Rr. Hasti (Journal of English Language and Pedagogy, 2024)
The objectives of this study are to: (1) describe the development of speaking materials for grade eleven students based on contextual language teaching and learning, and (2) reveal the efficacy of the speaking teaching materials in improving students' speaking skills. This research belongs to educational Research and Development (R&D), which uses the simplified six-step approach of Borg and Gall (1983). The six steps are as follows, (1) Research and information collecting was conducted by performing document analysis, class observation, interview, product testing, as well as expert’s judgements, (2) planning and drafting, (3) Draft revision by experts, (4) field testing which was conducted in grade eleven students, (5) Revision, and (6) Final product. The data collection technique used in this research consists of (1) document analysis, (2) classroom observation, and (3) interviews. It was made for obtaining the data for the target situation analysis and appropriateness of the design of speaking materials for grade eleven. The findings show that (1) learning materials that were designed in this research fulfilled the criteria of the R&D model, which is based on the students' needs, lack, and want. This textbook is designed based on the students’ needs, lacks, and wants. Furthermore, the speaking materials, as the product of this study, provide additional learning resources for students. The purpose of the learning is to prepare the students to learn more about speaking because speaking skills are more useful for communication.